Numerical Evaluation of Singular Multivariate Normal Distribution - KWONG, Koon Shing (Institutional Knowledge at Singapore Management University, 2000)
Presents an efficient and accurate method to evaluate multivariate normal probabilities with arbitrary singular correlation matrices. Singular distribution; Numerical integration; Statistical computation.